Prevalence of Hoarding Behavior Among Formerly Homeless Persons Living in Supported Housing. Issue 10 (October 2020) - Greig, Astrea; Tolin, David; Tsai, Jack
Abstract : Abstract: Hoarding disorder has become an official disorder in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ( DSM-5 ). Hoarding disorder affects approximately 1.5% to 5% of the general population, and there is no known literature that has examined the prevalence of hoarding disorder among homeless populations or those living in supported housing, although hoarding problems can jeopardize their housing situation. This study used the Clutter Image Rating to estimate the prevalence of possible hoarding behavior among 660 adults living in supported housing. The results indicate that 18.5% of supported housing residents had hoarding behavior, which is more than three times the prevalence reported in the general population. These results suggest that hoarding behavior and possibly hoarding disorder may be more prevalent among those with histories of homelessness and housing instability, which may be of concern because it may affect both housing and health statuses.